EFEKTIVITAS STRATEGI PEMBELAJARAN INDEX CARD MATCH TERHADAP HASIL BELAJAR SISWA PADA SUB MATERI TEORI HIBRIDISASI KELAS XI IPA SMA NEGERI 1 SUNGAI RAYA - Dinta Winisandia (Jurnal Ilmiah Ar-Razi, 2018)
The research was based on low learning outcome of XI IPA class student of SMAN 1 Sungai Raya in chemistry especially sub material of hybridization theory. This research aimed to determine difference in learning outcome between student taught by using index card match learning strategies with students taught without using index card match learning in the sub material of hybridization theory class XI IPA of SMAN 1 Sungai Raya. This research used Control Group Pretest-Posttest Design with the research subject was 29 control class students and 28 experiment class student XI IPA class SMAN 1 Sungai Raya. Techniques and data collection tools used learning result test, observation, and interview. The result of data analysis showed that the average value of pretest control class was 38,45 and the average value of posttest class was 52,60 while the average value of pretest experiment class was 21,25 and posttest average value is 75,13. Statistic analysis result U Mann-Whitney test showed the significance value of 0,000 that was smaller than α (0,000 < 0,05) which mean that there are differences in student learning outcome taught by using index card match learning strategy. The amount of increase in learning outcome was known from the calculations effect size value as big as 0,94 in high category as big as 82,64%. Therefore, index card match learning strategy can be applied to sub material hybridization theory to improve student learning outcome